FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KARET DI DESA LUBUK BANJAR KECAMATAN LUBUK RAJA KABUPATEN OGAN KOMERING ULU - Ema Pusvita, Fachrurozi, Septianita, (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2024)
Rubber is a plantation commodity that plays a very important role in Indonesia. Although Indonesia has the largest rubber area in the world, Indonesia is still the second largest producer of natural rubber after Thailand. Many factors affect rubber production. This study aims to analyze the factors that affect rubber production and calculate farmers' income from rubber farming. The study was conducted in the rubber production center in Lubuk Banjar Village, Lubuk Raja District, Ogan Komering Ulu Regency. The research method used in this study was the survey method. Sampling used the simple random sampling technique, with a sample size of 68 out of a total of 216 rubber farmers. The purpose of the study was analyzed using the Cobb Douglas production function, to see the factors that affect rubber production. While farm income was calculated using the income formula. The results showed that the factors that affect rubber production in Lubuk Banjar Village, Lubuk Raja District, OKU Regency were plant age, amount of fertilizer, number of workers, herbicides, and land area. Rubber farming income in Lubuk Banjar Village, Lubuk Raja District was Rp 4,054,772.64 per month.